2012
DOI: 10.1002/art.34613
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic progenitor cells respond to cartilage injury

Abstract: Styrene oligomers (Mn, 2500–3000 g/mol) with low polydispersity index and containing peroxidic groups within their structure were synthesized using a novel trifunctional cyclic radical initiator, diethylketone triperoxide (DEKTP), through nitroxide‐mediated radical polymerization (NMRP), using OH‐TEMPO. During the synthesis of the polystyrene (PS) oligomers, camphorsulfonic acid (CSA) was used to inhibit the thermal autoinitiation of styrene at the evaluated temperatures (T = 120–130°C). The polymerization rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
276
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(303 citation statements)
references
References 63 publications
(88 reference statements)
14
276
1
1
Order By: Relevance
“…It should be noted that the lack of HMGB1 expression in mice had detrimental effects on homeostasis of bone and cartilage (Taniguchi et al, 2007). Seol et al (2012) showed that injury to bovine cartilage and chondrocyte death stimulated the emergence of chondrogenic progenitor cells via HMGB1 release and RAGEmediated chemotaxis. This process could be inhibited by Glycrrhizin, a chelator of HMGB1 and anti-HMGB1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the lack of HMGB1 expression in mice had detrimental effects on homeostasis of bone and cartilage (Taniguchi et al, 2007). Seol et al (2012) showed that injury to bovine cartilage and chondrocyte death stimulated the emergence of chondrogenic progenitor cells via HMGB1 release and RAGEmediated chemotaxis. This process could be inhibited by Glycrrhizin, a chelator of HMGB1 and anti-HMGB1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we identified the characteristics of these chondrogenic progenitor cells (CPCs) isolated from injured articular cartilage. 21 These cells showed notable chemotatic activity, clonogenicity, and side populations like MSCs. On the other hand, they underexpressed cartilage-specific genes, such as type II, IX, and X collagens and aggrecan, compared with normal chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…21 The control cartilage in our explant model begins to deteriorate after *3 weeks, due possibly to the lack of mechanical stimulation in culture. This may not have been long enough to fully evaluate the potential for matrix regeneration in defects.…”
Section: Discussionmentioning
confidence: 99%
“…Although cell death and cartilage failure are correlated, the relationship between chondrocyte loss and cartilage degeneration is unknown. Some studies indicate chondrocyte loss precedes cartilage damage after injury and that chondrocyte repopulation in damaged areas can promote cartilage repair (13,14). Other studies indicate that injured chondrocytes produce factors, such as matrix metallopeptidase 13 (MMP13), ADAM metallopeptidase with thrombospondin type 1 motif 4 (ADAMTS4), and ADAMTS5, that cause cartilage degeneration (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%